Pengembangan Gim Edukasi Pengenalan Patung di DKI Jakarta Berbasis Desktop - Erick Richardo; Paramaresthi Windriyani (UNIVERSITAS KALBIS, 2022)
The purpose of this research is to develop a game to give players insight into the statues in DKI Jakarta, so that players can understand the history of these statues. The statues include: Diponegoro Statue, General Sudirman Statue, Moh. Husni Thamrin, Ismail Marzuki Statue, Chairil Anwar Statue, Small Gus Dur Statue, General Ahmad Yani Statue, DR. GSSJ Ratulangi, Hero Statue, Archer Statue, Statue of the Great General A.H. Nasution, Statue of Bung Karno. The method used in making this game is Game Development Life Cycle (GDLC). In the GDLC method, there are several stages, including: Initiation, Pre-production, Production, Testing, Beta, and Release. The result of this research is an educational game